Effects of icariside II on brain tissue oxidative stress and Nrf2/HO-1 expression in rats with cerebral ischemia-reperfusion injury - Li,Yan (2019)
Abstract Purpose: To investigate the effects of icariside II on brain tissue oxidative stress and Nrf2/HO-1 expression in rats with cerebral ischemia-reperfusion injury (CIRI). Methods: One hundred SD rats were randomly divided into sham-operated, model, and 5, 10 and 20 mg/kg icariside II groups, 20 rats in each group. The middle cerebral artery occlusion model (ischemia for 2 h followed by reperfusion for 24 h) was established in the later 4 groups. In later 3 groups, at reperfusion beginning, the rats were intragastrically administrated with 5, 10 and 20 mg/kg icariside II, respectively. After 24 h of reperfusion, the neurological severity score, cerebral water content and cerebral infarction volume, brain tissue oxidative stress indexes and Nrf2 and HO-1 protein expressions were determined. Results: Compared with model group, in 20 mg/kg icariside II group the neurological severity score, cerebral water content and cerebral infarction volume, brain tissue ROS content and MDA level were significantly decreased (P<0.05), and the brain tissue SOD, GSH-Px and catalase levels and Nrf2 and HO-1 protein levels were significantly increased (P<0.05). Conclusion: Icariside II can alleviate the CIRI in rats through reducing brain tissue oxidative stress and improving Nrf2/HO-1 expression.